Miniaturized spoof SPPs filter based on multiple resonators or 5G applications - Behnam Mazdouri (Nature Portfolio, 2021)
Abstract This paper presents a novel and compact band-pass filter based on spoof surface plasmon polaritons (SSPPs) concept for 5G applications. In the first place, an SSPPs unit cell including L-shaped grooves and its equivalent circuit model are introduced. The obtained results from dispersion analysis shows that cut-off frequency of the cell can be considerably decreased thanks to its geometrical configuration. In the second place, a miniaturized SSPP transmission line (TL) consisting of the proposed unit cell with cut-off frequency of 29.5 GHz is designed. Two mode convertors have been employed for efficient connection between coplanar waveguides and SSPP TL. Moreover, a new method based on loading one unit cell of SSPP TL by stub resonators is proposed in order to block a specific frequency band. An equivalent circuit model for the cell with the resonators is proposed to predict rejected frequency range. Thereafter, as an example of our method, a SSPPs filter operating at 26.5–29.5 GHZ is designed by means of connecting stub resonators with different lengths to provide close resonance frequencies. The circuit model, full wave simulation, and measurement results are in a good agreement. The results of proposed groundless SSPP TL and filter structures are promising to make groundless 5G applications possible.